Existential isolation and well-being in justice-involved populations - Sease, Thomas B.; Cox, Cathy R.; Knight, Kevin (Frontiers in Psychology, 2022)
Much work in psychology has focused on feelings of social isolation and/or loneliness. Only recently have psychologists begun to explore the concept of Existential Isolation (EI). Existential isolation is the subjective sense that persons are alone in their experience and that others are unable to understand their perspective. Existential isolation thus occurs when people feel that they have a unique worldview unshared by others. Measured as either a state or trait, empirical studies have shown EI undermines life meaning and decreases well-being; people scoring high on EI report lower levels of need satisfaction, purpose in life, and meaningfulness and increased death-related concerns. There is also a positive correlation between EI and anxiety, depression, and suicidal ideation. The purpose of this perspective paper is to review literature on EI and discuss its relevance to people who have been involved with the justice system. Given their higher rates of substance use, mental health difficulties, and trauma, this traditionally underserved population is particularly susceptible to compromised well-being. We theorize that EI may impede the impact of therapeutic interventions in justice settings as more isolated individuals may feel disjointed from their counselors and peers, thereby decreasing levels of treatment engagement, participation, satisfaction, and perceived social support. Professionals may be able to mitigate issues related to EI by an enhanced focus on establishing authenticity within the therapist-client relationship (e.g., empathy, perspective taking, compassion), connecting with clients via I-sharing (i.e., matching on a shared experience[s]), and/or encouraging active participation in client’s behavioral healthcare needs (e.g., self-reflection).